The Strategic Role of Remuneration Systems in Enhancing Employee Job Satisfaction and Productivity - Ardyan Adhijoyo; Danang Prasetya (PT. Mawadaku Sukses Solusindo, 2025)
The primary objective of this research is to examine the role of remuneration in enhancing job satisfaction and its subsequent influence on employee productivity within State Own Banking Services. The study employs a causal research design with a quantitative approach. A total of 187 employees were selected as respondents through purposive sampling. Data were gathered using a structured questionnaire and analyzed by employing the Partial Least Squares (PLS) method. The empirical results demonstrate that remuneration exerts a significant and positive impact on both job satisfaction and employee productivity. Furthermore, the analysis reveals that job satisfaction significantly contributes to the improvement of work productivity.